The Annual Premium of Life Insurance on The Joint-Life Status based on The 2011 Indonesian Mortality Table - Suryani, Stacia Litha; Ruswandi, Rudi; Faisol, Ahmad (Desimal: Jurnal Matematika, 2020)
Life insurance is insurance that protects against risks to someone's life. Joint Life Insurance is insurance where the life and death rules are a combination of two or more factors, such as husband-wife or parent-child, and if the first death occurs, then the premium payment process is stopped. The annual premium is the premium paid annually. In this study, the annual premium is calculated continuously with the equivalence principle based on the 2011 Indonesian Mortality Table.  The calculation shows that the amount of annual premiums for 2 (two) and 3 (three) people is not much different. The factors that influence the annual premium amount are the duration insurance period, age at signing the policy, interest rates, life chances, force of mortality, and the number of benefits.